Estrogenic and anxiolytic effects of the decoction of stem bark of Khaya anthotheca (Welw.) C.DC (Meliaceae) in ovariectomised Wistar rats - Germain Jean Magloire Ketcha Wanda; Franklin ZEMO GAMO; Sefirin DJIOGUE; Charline Florence AWOUNFACK; Dieudonne NJAMEN (International Journal of Phytomedicine, 2017)
Khaya anthotheca (Welw.) C.DC (Meliaceae) is a plant used in Cameroon to alleviate vaginal dryness in postmenopausal women and is also known to have anxiolytic properties.This work was designed to evaluate estrogen-like effects of this plant on primary estrogens targets of ovariectomized adult rats, as well as to evaluate its anxiolytic activities in the elevated plus-maze (EPM) test. In the 3-day uterotrophic assay, the extract increased (p < 0.01) the size of the vaginal epithelia and stimulated the acini differentiation of the mammary gland. In the EPM test, the extract increased the percentage of number of entries (p <0.05; p <0.01) and the percentage of time spent (p < 0.05) into open arms.Italso induced a decrease in percentage of number of entries (p < 0.05; p < 0.01) and the percentage of time spent (p < 0.05) into closed arms. The extract also induced an increase of total arms entries (p < 0.05; p < 0.01) and rearing (p < 0.05). Moreover, there was a decrease of defecation and grooming (p < 0.05; p < 0.01). These results suggest that K. anthotheca is endowed with estrogenic and anxiolytic properties, likely due to the presence of some estrogen-like compounds.